Analysis of adaptation processes in the educational environment of students with disabilities of junior courses - Kokhan S. T., Simonova V. O. (Interactive science, 2019)
the article discusses the existing problems associated with the adaptation of first-year students with disabilities, who have profound impairments of body function (totally blind, deaf, and lesions of the musculoskeletal system) in the educational process at the university. Cause-and-effect relationships were established in the existing difficulties of relationships with classmates, which depend both on the student and on the psychosocial climate in the group.
Keywords: студент; адаптация; университет; ограниченные возможности здоровья; инвалидность; disability; student; adaptation; university; study; учеба; limited health